ANALYSIS OF NETFLIX STREAMING SERVICES ON CUSTOMER LOYALTY IN INDONESIA - Fernando; Fendy Cuandra (Faculty of Economic and Business, University of Pasundan, 2023)
The increasingly rapid development of the economy and technology can affect people's daily lives. Purpose of this research is to test and analyze how much customer loyalty using Netflix is influenced by service quality and reputation mediated by customer trust and customer satisfaction in the Indonesian people. This study uses quantitative methods using descriptive statistics, then survey in this study was carried out by distributing questionnaires to the Indonesian people who were the object of research and the total sample that could be tested was 401 data. The research data was processed using the SmartPLS 3 application. Result data showed that all independent variables significantly affected customer loyalty of the Indonesian people, except quality of service on customer loyalty was not significant.